Conjunctival Tumors: Review of Clinical Features, Risks, Biomarkers, and Outcomes—The 2017 J. Donald M. Gass Lecture. Issue 2 (March 2017) - Shields, Carol L.; Chien, Jason L.; Surakiatchanukul, Thamolwan; Sioufi, Kareem; Lally, Sara E.; Shields, Jerry A.
Abstract : Abstract: : Conjunctival tumors encompass a broad range of diagnoses. The 3 most important malignant tumors include ocular surface squamous neoplasia (OSSN) (14%), melanoma (12%), and lymphoma (7%). Conjunctival malignancies are rarely found in children. Regarding OSSN, predisposing conditions include chronic solar radiation, immune deficiency (HIV), organ transplant, autoimmune conditions, xeroderma pigmentosum, and chronic exposure to cigarette smoke. OSSN is managed surgically or with topical/injection immunotherapy or chemotherapy. Metastasis occurs in <1%. Regarding melanoma, predisposing conditions include primary acquired melanosis (PAM), chronic nevus, and chronic solar radiation. Treatment of PAM or nevus can prevent melanoma. Melanoma management involves surgical resection with clean margins and avoidance of direct tumor manipulation ("no touch" technique). The first surgery is most important, to minimize tumor seeding. Biomarkers including BRAF, TERT, and PTEN provide information regarding risk for metastasis and allow for targeted antibiomarker therapies. Ten‐year risk for melanoma metastasis is 25%. Tumors >2 mm thickness or those located in fornix, caruncle, or orbit are at highest risk for metastasis. Regarding lymphoma, predisposing conditions include benign reactive lymphoid hyperplasia, immune deficiency (HIV), immune dysfunction, and chronic inflammation/infection ( Helicobacter pylori, Chlamydia psittaci ). The 4 most important subtypes include extranodal marginal zone lymphoma (ENMZL), follicular lymphoma, mantle cell lymphoma (MCL), and diffuse large B‐cell lymphoma. Treatment includes surgical resection, cryotherapy, radiotherapy, systemic chemotherapy, or targeted anti‐B‐cell therapy (rituximab). Lymphoma‐related survival (5‐year) depends on subtype and ranges from 97% (ENMZL) to 9% (MCL). Recognizing conjunctival tumors and understanding predisposing factors, biomarkers, and treatment strategies are vital to patient outcomes.